Review of the genus Relaba (Hemiptera: Cicadellidae: Typhlocybinae: Alebrini) and description of two new species from Argentina - Catalano, María Inés; Paradell, Susana L.; Dietrich, Christopher H. (Zootaxa, 2016)
The genus Relaba is reviewed, and two new species, R. forcipula n. sp. and R. globata n. sp. are added. Detailed morphological descriptions and illustrations of the new species, and a key to males of known species are provided.